"SCREEN TIME POLICE" APPLICATION DESIGN TO LIMIT AND CONTROL SOCIAL MEDIA USAGE FOR YOUNG ADULTS IN BANDUNG - Setiadjie, Alika Putri; Aditya, Dimas Krisna; Barlian, Yelly Andriani (eProceedings of Art & Design, 2024)
Excessive use of social media may potentially lead to an addiction that has negative effects on a person’s wellbeing. Indonesian young adults are particularlyvulnerable to be addicted to social media because Indonesian young adults use the most social media compared to other age groups and they have an average social media usage duration that exceeds the recommended usage. Apple, Android, and third-party developers have provided applications that is marketed to help users to limit and control their social media usage to overcome social media addiction. However, those applications are proven to be ineffective to limit and control social media usage due to the lack of restriction or due to the nature of the application itself. This research aims to design an alternative media that is able to effectively track, limit, and control social media usage bycombining the strengths and improving the weaknesses of the built-in and third-party applications in order to overcome social media addiction. To conduct this research, the author uses qualitative method to collect data, namely with observation, interview, literature study, and questionnaire. To analyze the data, the author uses matrix analysis. The final media that is created for this research is an application design. Benefits of this media is to be able to give an effective alternative to limit and control social media usage in young adults.. Keywords: social media addiction, screen time, young adults